1992
DOI: 10.1038/bjc.1992.310
|View full text |Cite
|
Sign up to set email alerts
|

CMV chemotherapy for advanced transitional cell carcinoma

Abstract: Between May 1986 and September 1990 a total of 43 patients with metastatic transitional cell carcinoma (TCC) of the urinary tract have been treated at our institution with combination chemotherapy (CMV) consisting of cisplatin 100 mg m-2 i.v. day 2; methotrexate 30 mg m-2 i.v. days 1.8; and vinblastine 4 mg m-2 i.v. days 1.8. Chemotherapy was recycled on day 22 and continued for a maximum of six cycles in responding patients. Of 33 patients with measurable disease 8 (24%) achieved a complete remission (CR). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 16 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In the Intergroup study, which compared M-VAC with cisplatin, the most important prognostic factors for favourable outcome were a good performance status, weight loss of <10%, and lack of visceral metastases (Loehrer et al, 1992 (1985), patients with CR had the best survival, whereas PR was not related to a beneficial long-term survival. Jeffery and Mead (1992) suggested that patients with advanced ureteric or renal pelvis TCC represented a good prognostic group. Owing to lack of relevant information this factor could not be analysed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In the Intergroup study, which compared M-VAC with cisplatin, the most important prognostic factors for favourable outcome were a good performance status, weight loss of <10%, and lack of visceral metastases (Loehrer et al, 1992 (1985), patients with CR had the best survival, whereas PR was not related to a beneficial long-term survival. Jeffery and Mead (1992) suggested that patients with advanced ureteric or renal pelvis TCC represented a good prognostic group. Owing to lack of relevant information this factor could not be analysed in this study.…”
Section: Resultsmentioning
confidence: 99%